2017
DOI: 10.1038/s41598-017-01112-9
|View full text |Cite
|
Sign up to set email alerts
|

Large spin Hall angle in vanadium film

Abstract: We report a large spin Hall angle observed in vanadium films sputter-grown at room temperature, which have small grain size and consist of a mixture of body centered tetragonal (bct) and body centered cubic (bcc) structures. The spin Hall angle is as large as θ V = −0.071 ± 0.003, comparable to that of platinum, θ Pt = 0.076 ± 0.007, and is much larger than that of bcc V film grown at 400 °C, θ V_bcc = −0.012 ± 0.002. Similar to β-tantalum and β-tungsten, the sputter-grown V films also have a high resistivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…2f, the magnitude of V SP varies negligibly with increasing temperature in Pt/YIG sample, in sharp contrast to the results from VO 2 samples (Supplementary Note 5). Moreover, we note that V SP exhibits opposite signs for Pt and VO 2 samples under the same measurement configuration, indicating that VO 2 has a negative spin Hall angle, the same as pure metallic vanadium 9,24 .…”
Section: Resultsmentioning
confidence: 79%
“…2f, the magnitude of V SP varies negligibly with increasing temperature in Pt/YIG sample, in sharp contrast to the results from VO 2 samples (Supplementary Note 5). Moreover, we note that V SP exhibits opposite signs for Pt and VO 2 samples under the same measurement configuration, indicating that VO 2 has a negative spin Hall angle, the same as pure metallic vanadium 9,24 .…”
Section: Resultsmentioning
confidence: 79%
“…This could explain the large SHAs observed from experiments on many 3d transition metals. [26][27][28][29][30][31] Our finding not only enriches understanding of the intrinsic OHE and SHE, but also widens material choice to weak SOC materials for spintronics. Moreover, our microscopic analysis based on the electronic band structure provides a route to enhancing these effects, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…22 Most studies on the SHE so far have focused on 4d and 5d transition metals because large SOC in these materials tends to generate large SHE. [11][12][13][14][15][16] For 3d transition metals, on the other hand, theoretical study is limited 14 despite the fact that several experiments have reported that 3d transition metals such as V, 26 Cr, 27 Ni, 28 and Py 29 exhibit large SHAs. This motivates us to study the OHE and SHE in 3d transition metals.…”
Section: Ohe and She In Weak Soc Metalsmentioning
confidence: 99%
“…Since θ SH is strongly correlated with the material atomic number, various HMs, such as Pt, Ta, W, V, Ir, and Hf, have been explored for SOT study . Among these materials, Pt is the most well studied, and it is found of a large positive SHA.…”
Section: Manipulation Of Sotmentioning
confidence: 99%